THE TRADITION OF WOMEN PROPOSING TO MEN FROM THE PERSPECTIVE OF ISLAMIC LAW AND CULTURE IN THE COMMUNITIES OF LAMONGAN AND TRENGGALEK - Muhammad Ma’ruf Burhanudin; Ita Rahmania Kusumawati (Adisam Publisher, 2025)
Proposal is a process conducted prior to marriage with the aim of establishing a matchmaking relationship between a man and a woman. In Payaman Village, Solokuro Subdistrict, Lamongan Regency, and Gandusari Village, Gandusari Subdistrict, Trenggalek Regency, there is a unique tradition where women propose to men. This tradition is rooted in customs passed down by religious and community leaders from generation to generation. This study aims to understand the implementation of this tradition, along with the perspectives of Islamic law and local wisdom related to the practice. The research method used is qualitative, with interviews conducted with religious and community figures involved in the practice. Theoretical and discussion sections must examine the religious arguments demonstrating that this tradition does not violate Islamic law. This tradition has an impact on strengthening women's roles, balancing power, improving communication, enhancing marriage quality, and enabling social adjustment. The results of the study show that the tradition of women proposing to men is based on long-standing customary practices preserved by the local community and, most importantly, does not violate Islamic law.